Pengaruh Pola Asuh Orang Tua Dan Disiplin Belajar Terhadap Hasil Belajar Pendidikan Agama Kristen Siswa Kelas V Sekolah Dasar - Komaling, Olga N. (Peneliti.net, 2024)
The aim of this research is to prove the influence of parenting patterns on learning outcomes, learning discipline on learning outcomes, and the influence of parental parenting and learning discipline on learning outcomes. The research method used is survey. The population in this study was all fifth grade students at Providence Elementary School, Manado City, totaling 42 people. The research data comes from primary data in the form of questionnaires and the secondary data used is data on Christian Religious Education learning outcomes in the mid-semester exam. The data analysis technique uses descriptive statistical analysis techniques, the data testing stages use the normality test, linearity test, then multiple linear regression analysis tests are carried out, and hypothesis testing uses partial tests or t tests and simultaneous tests or F tests. The research results show (1) there are The influence of parental parenting on the learning outcomes of Christian Religious Education for fifth grade elementary school students. The variable parenting style (X1) as in table 4.22 above obtained a t count of 1.415 with a probability of 0.000 < 0.05. (2) There is an influence of learning discipline on the learning outcomes of Christian Religious Education for fifth grade elementary school students. The learning discipline variable (X1) as in table 4.22 above obtained a t count of 1.169 with a probability of 0.000 < 0.05. (3) there is an influence of parental parenting and learning discipline on the learning outcomes of Christian Religious Education for fifth grade elementary school students. This is proven by the calculated F of 1.555 with a probability of 0.000 which is a value below 0.05. Therefore, to improve learning outcomes, you must pay attention to and understand the factors of parenting styles and the application of student learning discipline.